Visuelle Linguistik Zur Genese, Funktion und Kategorisierung von Diagrammen in der Sprachwissenschaft - Bubenhofer, Noah (Linguistik - Impulse & Tendenzen, 2020)
Graphics and diagrams are important in linguistics: they visualise analysis findings, illustrate theoretical concepts and make it possible to analyse data in the first place. But how do they influence the generation of insights? What effect do they have on linguistic data? This book examines diagrammatical practices in linguistics and develops a methodology of visual linguistics.